Effect of method of Imperata cylindrica management on maize grain yield in the derived savanna of southwestern Nigeria - Akobundu, I.; Ekeleme, F. (Wiley, 2000)
Field studies were conducted in 1991 and 1992 on a sandy loam soil in the derived savanna zone of south-western Nigeria to assess the effect of the underground organs of Imperata cylindrica (L.) Raeuschel on maize grain yield. Total dry matter of I. cylindrica in abandoned arable land averaged 16 t ha−1 and rhizomes contributed 56% of this. Rhizome removal from soil before planting maize significantly increased maize yield relative to hoe tillage or slashing of I. cylindrica shoots before planting maize. Digging up rhizomes before planting maize and weeding the crop twice gave a yield reduction of only 23% compared with weed-free crops with rhizomes removed. Grain yield reduction was 51% in plots where rhizomes were only fragmented by hoe tillage and the crop was weeded twice. Grain yield was 62% less when maize was grown in slashed plots with intact rhizomes that were weeded four times (farmers’ practice). Slashing without additional weeding resulted in crop failure in maize.